Arcade at Horniman Circle - Ghosh, Ayan (2023)
Bombay Green was a hub of cotton trading before the traders were relocated to Colaba Causeway in 1838. Thereafter, Bombay Green was lying derelict, although the Agri-Horticultural Society made some effort to convert it into a public garden. Finally, in 1863, Police Commissioner Charles Forjett proposed to convert the Green into a Circle.